Knowledge audit on the implementation of knowledge management in public sector research institute in Malaysia: a case study - Zulkifli, Harlisa; Abdullah, Mohammad Fikry; Ibrahim, Mardhiah (2016)
Knowledge Management (KM) is a strategic initiative essential for any organisation to succeed.This paper discusses the evaluation of KM initiatives in the Malaysian Government Research Institute by performing knowledge audit.The evaluation was conducted to test the effectiveness of the current KM initiatives adopted by National Hydraulic Research Institute of Malaysia (NAHRIM) and to identify shortcomings that exist for the purpose of improvement.The methodology of the study involved an initial study by operating the company visit and literature on four other organisations that have successfully implemented the KM as a benchmark.Then, a survey was carried out to the employees of NAHRIM to identify their awareness; and the interviews were conducted among Top Management Officers of NAHRIM to gather their opinions towards current KM initiatives. In the final section of this paper, recommendations are presented as the results of the evaluation that has been carried out.